KESIAPAN GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA - Agun Sutrianto; Rahmi; Wulan Gontina; Rayandra Asyhar; Muhammad Rusdi (EDU RESEARCH, 2024)
This study aims to determine the readiness of teachers who teach in schools that are not driving schools in implementing the independent curriculum in the 2024/2025 school year. The population in this study were elementary, junior high, and high school / vocational school teachers in Jambi city, Padang city and Banyuasin Regency. The technique used in this study is a non-probality sampling technique, namely Quota sampling. Data collection through a questionnaire with the help of google form which contains 10 closed statements with a choice of 5 scales and 1 open statement. The data collected was analysed with the help of excel and then converted into qualitative data. Based on the analysis, it can be concluded that teachers in Jambi City, Padang City and Banyuasin Regency are ready to implement the independent curriculum in the 2024/2025 school year.